Pengaruh Kualitas Pelayanan Dan Lokasi Terhadap Keputusan Pembelian Gas LPG 3kg Pada Pangkalan Gas Tegar Jaya Abadi - Ahmed Luthfi Chaniago; Tri Lestira Putri Warganegara (Politeknik Negeri Ambon, 2023)
This study aims to determine whether the quality of service and location together influence the purchasing decision at the Tegar Jaya Abadi Gas Base. The population of this study are consumers of the Tegar Jaya Abadi Gas Base, with the Slovin formula it is known that the sample in the study is 100 people. The method of analysis using Multiple Linear Regression analysis. Based on theoretical studies and the results of data analysis, it can be concluded that (1) The results of the t-test hypothesis of the independent variable (Quality of Service) have a positive and significant influence on the dependent variable (Purchase Decision). (2) The results of the t-test hypothesis of the independent variable (Location) have a positive and significant influence on the dependent variable (Purchase Decision). (3) The results of the f hypothesis test for the variable Service Quality (X1) and Location (X2) together have a positive and significant influence on the Purchase Decision variable (Y). .